2020
DOI: 10.1038/s41419-020-02912-0
|View full text |Cite|
|
Sign up to set email alerts
|

ELABELA attenuates deoxycorticosterone acetate/salt-induced hypertension and renal injury by inhibition of NADPH oxidase/ROS/NLRP3 inflammasome pathway

Abstract: ELABELA (ELA), a 32-residue hormone peptide abundantly expressed in adult kidneys, has been identified as a novel endogenous ligand for APJ/Apelin receptor. The aim of this study was to investigate the role of ELA in deoxycorticosterone acetate (DOCA)/salt-induced hypertension and further explore the underlying mechanism. In DOCA/salt-treated rats, the mRNA level of ELA greatly decreased in the renal medulla. Next, overexpression of ELA in the kidney was found to attenuate DOCA/salt-induced hypertension and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Moreover, using immunostaining, we also found increased oxidative stress during diabetic corneal wound closure, characterized by aggravated ROS accumulation, and elevated expression of NADPH oxidase 2 (NOX2) and NOX4 in the corneal epithelial layer (Supplementary Fig. 2), which was reported to be related to NLRP3 inflammasome activation [27]. Taken together, the findings indicated that the sustained activation of NLRP3 inflammasome probably contributed to the postponed diabetic corneal wound closure.…”
Section: The Nlrp3 Inflammasome Was Hyperactivated During Diabetic Corneal Wound Healingmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, using immunostaining, we also found increased oxidative stress during diabetic corneal wound closure, characterized by aggravated ROS accumulation, and elevated expression of NADPH oxidase 2 (NOX2) and NOX4 in the corneal epithelial layer (Supplementary Fig. 2), which was reported to be related to NLRP3 inflammasome activation [27]. Taken together, the findings indicated that the sustained activation of NLRP3 inflammasome probably contributed to the postponed diabetic corneal wound closure.…”
Section: The Nlrp3 Inflammasome Was Hyperactivated During Diabetic Corneal Wound Healingmentioning
confidence: 53%
“…Combined with the overexpression of NADPH oxidase (NOX2 and NOX4) during diabetic corneal wound healing, these findings mechanistically demonstrated that the AGEgenerated ROS promoted NLRP3 inflammasome activity and inflammatory cascades, resulting in postponed diabetic corneal wound closure and impaired nerve regeneration. As previous studies supported that the ROS derived from NADPH oxidase and mitochondria both contributed to NLRP3 inflammasome activation [27,[43][44][45][46][47][48], further studies are required to determine which kind of ROS promotes AGE-induced NLRP3 inflammasome activation and delayed diabetic corneal wound healing, mitochondria-or NADPH oxidase-generated ROS.…”
Section: Discussionmentioning
confidence: 92%
“…Here, we found that chronic infusion of Elabela is more effective than Ape13 in protecting salt-loaded hypertensive rats from renal dysfunction, kidney hypertrophy, and remodeling. Accordingly, Elabela treatment was recently reported to preserve the glomerular structure, to prevent renal fibrosis and to block the expression of fibrosis-related genes in the kidneys of Dahl salt-sensitive rats on a high-salt diet and deoxycorticosterone acetate/salt-treated rats (Schreiber et al, 2017;Chen et al, 2020b;Xu et al, 2020). Consistently, recent clinical data have shown, in contrast to Ape13, that the decrease in serum Elabela levels is also strongly associated with deterioration of renal function and worsening stages of chronic kidney disease (Lu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that miRNAs are biomarkers and therapeutic targets (37)(38)(39)(40). Thus, we constructed a miRNA-mRNA interaction network to uncover the underlying molecular mechanism in hypertensive renal injury.…”
Section: Discussionmentioning
confidence: 99%